Affiliation to alcoholics anonymous or narcotics anonymous among patients attending an English specialist addiction service. Issue 4 (23rd October 2019) - Day, Edward; Kirberg, Sabrina; Metrebian, Nicola
Abstract : Purpose: Attendance at alcoholics anonymous (AA) or narcotics anonymous (NA) meetings and affiliation with the fellowship has potential benefits for people with alcohol or drug use disorders. This effect is present whether or not the individual attends professional treatment services, but the two process can have a synergistic effect. Limited information exists about the extent to which people attending UK specialist treatment services also attend AA/NA and their views about such attendance. The paper aims to discuss these issues. Design/methodology/approach: A cross-sectional survey of 200 consecutive attendees at the specialist treatment service in an English region was conducted between January and April 2018. A measure of past attendance and affiliation with AA/NA (AAAS) and a scale designed to quantify future readiness to attend (Survey of Readiness for Alcoholics Anonymous Participation) were administered and anonymously linked to data supplied to the National Drug Treatment Monitoring Service (NDTMS). Findings: A minority of the sample had ever attended an AA meeting (31 per cent, n =59) or an NA meeting (41 per cent, n =79), and only 14 per cent ( n =27) and 24 per cent ( n =45) had attended an AA or NA meeting, respectively, in the past year. Only two variables significantly predicted level of readiness to attend AA or NA in a regression model: attended more AA/NA meetings in the past ( ß =0.149, p =0.036) and previous level of participation (AAAS score) ( ß =0.409, p < 0.001). Practical implications: A significant proportion of attendees of a specialist drug and alcohol treatment service had never attended AA/NA, despite many positive views about their potential benefits. Given the established benefits of attending AA/NA meetings and participating in the AA or NA fellowship, these results suggest that professional treatment services should do more to explain the process and challenge preconceived ideas about how they operate. Originality/value: The authors are not aware of any published research that captures the rates of attendance of and participation in both AA and NA groups in a UK-based community treatment sample. These results may therefore provide a baseline for evaluating the impact of interventions to increase attendance/participation, and also provide some insight into the potential barriers to attendance in this population.